Kewargaan dan Kolaborasi Pemecahan Masalah Publik : Studi Isu Sampah di Kota Kupang - Sayrani, Laurensius P.; Tamunu, Lenny M. (Faculty of Public Health, Nusa Cendana University, 2020)
This article intends to examine the collaboration amongst actors in solving public issues, specifically in the topic of waste management in the Kupang city. Methodologically, the issue was disclosed using qualitative methods based on the descriptive survey, structured interviews, and in-depth interviews. Kupang City grow rapidly both in the aspect of social and economy, as a consequence, load of trash is inevitable along with the development. Otherwise, very little attention was paid to the waste management and people tended to recognise it as insignificant issue,constructed as interpersonal issues, and typically as a private matter. This article aims to demonstrate Kupang residents’ perception towards trash as a public matter. On that point, people awareness toward public issues in this article, which is named as “citizenship” become vital. Without this, problem including waste issue will be receiving limited response. Once it comes to its turn, collective action as a prerequisite for constructive problem solving in public relations would be weakened. It appears that the issue is about the amount of waste in the areas that are fully accessible to the public, for example; markets and housing areas. Waste is poorly managed in these two areas. On the other hand, formal institutional collaboration between government in the local government, the provincial government, and the neighbour district in Kupang district’s government also It appeared to have been poorly managed. This study suggests the need for a non-hierarchical forum that is concerned with decision-making process (not merely consultative) which facilitates the emergence of community control to alleviate